Voltammetric and amperometric sensors for determination of epinephrine: A short review (2013-2017) - Hadi Beitollahi; Mohadeseh Safaei; Somayeh Tajik (Journal of Electrochemical Science and Engineering, 2018)
The present review focuses on voltammetric and amperometric methods applied for determination of epinephrine (EP) in last five years (2013-2017). Occurrence, role and biological importance of EP, as well as non-electrochemical methods for its assessment, are firstly reviewed. The electrochemical behavior of EP is then illustrated, followed by a description of the voltammetric and amperometric methods for EP content estimation in various media. Different methods for development of electrochemical sensors are reviewed, starting from unmodified electrodes to different composites incorporating carbon nanotubes, ionic liquids or various mediators. From this perspective, the interaction between functional groups of the sensor material and the analyte molecule is discussed, as it is essential for analytical characteristics obtained. The analytical performances of the voltammetric or amperometric chemical and biochemical sensors (linear range of analytical response, sensitivity, precision, stability, response time, etc.) are highlighted. Numerous applications of EP electrochemical sensors in fields like pharmaceutical or clinical analysis where EP represents a key analyte, are also presented.